Three-dimensional printed electrode and its novel applications in electronic devices - Foo, Chuan Yi; Lim, Hong Ngee; Mahdi, Mohd Adzir; Wahid, Mohd Hanif; Huang, Nay Ming (Nature Research, 2018)
Three-dimensional (3D) printing technology provides a novel approach to material fabrication for various applications because of its ability to create low-cost 3D printed platforms. In this study, a printable graphene-based conductive filament was employed to create a range of 3D printed electrodes (3DEs) using a commercial 3D printer. This printing technology provides a simplistic and low-cost approach, which eliminates the need for the ex-situ modification and post-treatment of the product. The conductive nature of the 3DEs provides numerous deposition platforms for electrochemical active nanomaterials such as graphene, polypyrrole, and cadmium sulfide, either through electrochemical or physical approaches. To provide proof-of-concept, these 3DEs were physiochemically and electrochemically evaluated and proficiently fabricated into a supercapacitor and photoelectrochemical sensor. The as-fabricated supercapacitor provided a good capacitance performance, with a specific capacitance of 98.37 Fg−1. In addition, these 3DEs were fabricated into a photoelectrochemical sensing platform. They had a photocurrent response that exceeded expectations (~724.1 μA) and a lower detection limit (0.05 μM) than an ITO/FTO glass electrode. By subsequently modifying the printing material and electrode architecture, this 3D printing approach could provide a facile and rapid manufacturing process for energy devices based on the conceptual design.